Influence of Strategic Procurement Management on The Performance of State Corporations in Kenya - Basweti, Michael Nyangate; Achuora, Dr. John (International Journal of Supply Chain and Logistics, 2020)
Purpose: The purpose of the study was to establish whether strategic procurement management has contributed to the performance of state corporations in Kenya. Methodology: The study employed a descriptive research design; the researcher preferred this method because it allowed an in-depth study of the subject. The target population was all the 187 heads of procurement of the state corporations in Kenya. From the four strata, a sample of 127 was selected using simple random sampling. Semi-structured questionnaires were administered to collect qualitative and quantitative data. Once collected, data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 21. Results: In regard to inventory management system, the regression coefficients of the study show that it has a significant influence of 0.561 on performance of state corporations. Second in regard to strategic sourcing, the regression coefficients of the study show that it has a significant influence of 0.198 on performance of state corporations. With regard to supply base leveraging, the regression coefficients of the study show that it has a significant influence of 0.112 on performance of state corporations. Lastly, in regard to the fourth objective, the regression coefficients of the study show that it has a significant influence of 0.019 on performance of state corporations. Conclusion: Based on the findings, the study concluded that supply base leveraging, inventory management system, e-procurement and strategic sourcing have a positive relationship with performance of the state corporations. Policy Recommendation: The study recommended that public institutions should embrace strategic procurement management so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained.